Tasa efectiva del impuesto a la propiedad inmueble en Puerto Rico: análisis de caso de la implementación del impuesto predial en el municipio de Guaynabo (2011)
While trivial to the central government, property tax collections are the main source of revenues for municipalities in Puerto Rico, and almost every other country in the American continent. This paper empirically analyses the effective property tax rate in Puerto Rico intending to establish its impact on equity over the complete tax system. The general results applies to all jurisdictions not showing due diligence assessing the actual value of properties for taxation purposes, and proves that the implementation of the property tax in Puerto Rico is not directly imposed over the wealth derived from the real estate ownership and is in fact regressive.